INTEGRATED DESIGN AND EVALUATION OF LOGISTIC NETWORKS: ORIENTED PLACEMENT OF THE ORDER PENETRATION POINT - Klingebiel, Katja; Hellingrath, Bernd; Pires, Sílvio; Scavarda, Luiz Felipe (Brazilian Journal of Operations & Production Management, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->The placement of the order penetration point (OPP) is a key decision in automotive supply chains since the product will be differentiated according to the customers’ requirements only after the OPP. From a marketing perspective variety proliferation is encouraged. Yet, competition has shifted from individual firms to global supply chains and under given market uncertainty the significance of supply chain flexibility is increasing. Upstream however, the expansion of outsourcing, supplier rationalization and lean production practices has yielded substantial progress in terms of supply chain efficiency. In order to economically operate the supply chain, the positioning of order penetration points is vital to inflict as much downstream process and product flexibility to be amenable to changing market demand and to guarantee as much upstream stability to allow for accurate and risk-controlled planning of cost-efficient supply chain processes. This paper identifies and analyses the main factors related to OPP problems and presents a method for OPP positioning under a supply chain perspective, integrating the influence of product diversity and supply chain flexibility over a complete product life-cycle systematically.